2018
DOI: 10.1155/2018/7078214
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Taste Receptors Mediated ROS-NLRP3 Inflammasome Signaling Activation: Implications for Diabetic Nephropathy

Abstract: Previous studies demonstrated that ROS-NLRP3 inflammasome signaling activation was involved in the pathogenesis of diabetic nephropathy (DN). Recent research has shown that sweet taste receptors (STRs) are important sentinels of innate immunity. Whether high glucose primes ROS-NLRP3 inflammasome signaling via STRs is unclear. In this study, diabetic mouse model was induced by streptozotocin (STZ) in vivo; mouse glomerular mesangial cells (GMCs) and human proximal tubular cells were stimulated by high glucose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…ROS signal pathway has been shown to be closely related to the DN (Qiu and Tang, 2016). Zhou et al (2018) proved that high glucose can induce the activation of ROS-meditated activation of the NLRP3 inflammasome. Xu et al (2018) showed that TXNIP can induce the oxidative stress response in glomerular mesangial cells, while Tan et al (2015) found that TXNIP inhibited tubule-interstitial compartment from acting as an important meditator in the process of tubule-interstitial fibrosis in DN.…”
Section: Inflammasomes In Diabetic Nephropathymentioning
confidence: 99%
“…ROS signal pathway has been shown to be closely related to the DN (Qiu and Tang, 2016). Zhou et al (2018) proved that high glucose can induce the activation of ROS-meditated activation of the NLRP3 inflammasome. Xu et al (2018) showed that TXNIP can induce the oxidative stress response in glomerular mesangial cells, while Tan et al (2015) found that TXNIP inhibited tubule-interstitial compartment from acting as an important meditator in the process of tubule-interstitial fibrosis in DN.…”
Section: Inflammasomes In Diabetic Nephropathymentioning
confidence: 99%
“…135 HG and AGEs induce the production of ROS, 139 which activates thioredoxin-interacting protein (TXNIP)/NLRP3 inflammasome in glomerular mesangial cells, 136 podocytes, 139 and proximal tubular cells. 137 The most convincing evidence illustrating the role of NLRs in diabetic nephropathy comes from NLRP3 knockout mice which fail to develop diabetes-induced kidney abnormalities. 141 Receiver operating characteristic analysis revealed that the relative expression of NLRP3 mRNA is a useful biomarker of nephropathy in T2DM patients.…”
Section: Nlrs In Diabetic Nephropathymentioning
confidence: 99%
“…In long-standing diabetes, cardiac and vascular injury is, to a large extent, caused by HG-activated NLRP3 inflammasome, which drives inflammatory responses by not only inducing cytokines, such as IL-1β and IL-18, but also causing pyroptosis. 137,157,158 Hyperglycemia has been shown to activate the NLRP3 inflammasome in various cell populations of the heart, including cardiomyocytes and cardiofibroblasts, 157,[159][160][161] leading to cardiac inflammation, fibrosis, and apoptosis. 162,163 HG-induced activation of NLRP3 can also be regulated by Syk/JNK and TLR4/ NF-κB pathways.…”
Section: Nlrs In Diabetic Cardiomyopathymentioning
confidence: 99%
“…Welcome reviewed recent evidence to demonstrate that the sweet taste receptor heterodimer T1R2/T1R3 plays a crucial role in cognitive functioning, suggesting that dysfunctions in sweet taste receptor signaling may underlie cognitive impairment in some brain pathologies [122]. Dysfunctions in sweet taste receptor signaling were also associated with inflammatory response pathway [123]. The study showed that sweet taste receptors function as pivotal immune sentinels, revealing the downregulation of the key components of the taste signaling cascades such as α-gustducin, phospholipase C β2, and monovalent selective cation channel TRPM5, contributing to cognitive impairment [123].…”
Section: Non-nutritive Sweeteners Interfere With Learned Responsesmentioning
confidence: 99%
“…Dysfunctions in sweet taste receptor signaling were also associated with inflammatory response pathway [123]. The study showed that sweet taste receptors function as pivotal immune sentinels, revealing the downregulation of the key components of the taste signaling cascades such as α-gustducin, phospholipase C β2, and monovalent selective cation channel TRPM5, contributing to cognitive impairment [123].…”
Section: Non-nutritive Sweeteners Interfere With Learned Responsesmentioning
confidence: 99%